2022
DOI: 10.1021/acscatal.2c02689
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Electrocatalytic Conversion of Food Waste to Ethylene via Succinic Acid as the Central Intermediate

Abstract: Ethylene is an important feedstock in the chemical industry, but currently requires production from fossil resources. The electrocatalytic oxidative decarboxylation of succinic acid offers in principle an environmentally friendly route to generate ethylene. Here, a detailed investigation of the role of different carbon electrode materials and characteristics revealed that a flat electrode surface and high ordering of the carbon material are conducive for the reaction. A range of electrochemical and spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…As can be seen in Fig. 5C, the signals of carbon-centered alkyl radical (•CH 2 R) and hydroxyl radical (•OH) are observed for Pd 1 -TiO 2 (36,63). The alkyl radical is recognized as the key intermediate for Kolbe oxidations (15,64).…”
Section: Photocatalytic Mechanistic Studymentioning
confidence: 80%
“…As can be seen in Fig. 5C, the signals of carbon-centered alkyl radical (•CH 2 R) and hydroxyl radical (•OH) are observed for Pd 1 -TiO 2 (36,63). The alkyl radical is recognized as the key intermediate for Kolbe oxidations (15,64).…”
Section: Photocatalytic Mechanistic Studymentioning
confidence: 80%
“…11d and e). 87 The use of a graphite anode resulted in the highest FE of ethylene (27.5%) at 2.8 V vs. RHE in 0.08 M succinic acid aqueous solution ( pH 10). According to the DFT calculation and EPR spin-trapping experiment results, the ECDX of succinic acid undergoes sequential decarboxylation via monoalkyl-radical species; however, the formation of diradical species via direct 2e − oxidation cannot be neglected.…”
Section: Dicarboxylic Acidsmentioning
confidence: 94%
“…11 To this end, the photooxidation of food wastes and nonrecycled plastics has recently become an emerging topic in the field. 11,[37][38][39][40][41][42][43][44] The chemical composition of food waste varies greatly. Due to their hydrophobicity and typically chemically inert hydrocarbon chain, photoreforming fats in an aqueous solution is more difficult than photoreforming proteins composed of long chains of amino acid residues (Table 1).…”
Section: Photoreformingmentioning
confidence: 99%
“…Controlling the oxidation half-reaction is essential to produce high-value organic products instead of CO 2 . 21,41 In addition, pre-treatment, including physical pre-treatment (such as crushing, shredding, and grinding) and chemical pre-treatment (such as hydrolysis and solubilization under highly alkaline or acidic conditions), is one of the most critical barriers to the practical application of the current photocatalytic reforming systems, adding significant cost and time to the overall process. Recently, it was demonstrated that metal salt hydrate solutions allowed for the complete solubilization of biomass and could be used as a reaction medium for the photocatalytic reforming of lignocellulose to produce H 2 and organic products under more benign conditions than the typically required extremely alkaline aqueous solutions, though the photocatalysts suffered from partial deactivation due to metal salt hydrate adsorption, necessitating future development.…”
Section: Photoreformingmentioning
confidence: 99%